2014
DOI: 10.3389/fvets.2014.00019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Vaginal Microbiota of Ewes and Cows Reveals a Unique Microbiota with Low Levels of Lactobacilli and Near-Neutral pH

Abstract: Although a number of common reproductive disorders in livestock involve bacterial infection, very little is known about their normal vaginal microbiota. Therefore, we sought to determine the species composition of sheep and cattle vaginal microbiota. Twenty Rambouillet ewes and twenty crossbred cows varying in age and reproductive status were sampled by ectocervicovaginal lavage. We amplified and sequenced the V3–V4 region of the 16S ribosomal RNA (rRNA) contents yielding a total of 907,667 high-quality reads.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
149
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 47 publications
16
149
2
2
Order By: Relevance
“…Vaginal microflora investigations in different reproductive periods acquired a 55.6% rate of bacterial growth in pregnant sheep. These results, Enterobacter species, Escherichia coli and Lactobacilli were the most isolated bacteria (Zaid, 2009). Swartz (2014 characterized vaginal microbiota of ewes and reported that Aggregatibacter spp.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Vaginal microflora investigations in different reproductive periods acquired a 55.6% rate of bacterial growth in pregnant sheep. These results, Enterobacter species, Escherichia coli and Lactobacilli were the most isolated bacteria (Zaid, 2009). Swartz (2014 characterized vaginal microbiota of ewes and reported that Aggregatibacter spp.…”
Section: Discussionmentioning
confidence: 83%
“…Swartz (2014 characterized vaginal microbiota of ewes and reported that Aggregatibacter spp. and Streptobacillus spp were the most abundant agents (Swartz et al, 2014). In this study, we planned to determinate normal microbial flora in pregnant ewes based on vaginal cytology and microbiology.…”
Section: Discussionmentioning
confidence: 99%
“…51 Some other isolates formerly assigned to S. moniliformis exist, from which S. notomytis from a spinifex hopping mouse (Notomys alexis) and from black rats (Rattus rattus) and S. ratti from an asymptomatically colonized black rat were recently described. 52,53 Contrarily to Nolan et al, 54 various potentially novel Streptobacillus species and phylotypes consistent with operational taxonomic units have been identified in the last few years from Atlantic salmon 55 and microbiomes of digestive tracts in dolphins and sea lions, [56][57][58] upper respiratory tracts in cotton rats, 37 digestive tracts in dogs, 39,59,60 intestinal tract of a ducks, 61 genital tracts in livestock, 32 and skin and gut microbiomes in humans (Fig. 1).…”
Section: Host Spectrummentioning
confidence: 88%
“…4,13,[16][17][18][19][20][21][22] Recently, various publications suggest that Streptobacillus species might be far more common and distributed in the environment or as commensal microbiota than previously thought. 32,37,[59][60][61][62][63] It could recently be shown that the natural reservoir for the very rare cases of human S. hongkongensis infection known to date is indeed the human oropharynx à and presumably not an unidentified animal or environmental reservoir. 49 Despite a certain amount of annually published case reports, most of which have solely used 16S rRNA sequencing alone for definite diagnosis, there has not been much progress in the diagnosis of acute clinical cases of RBF in the last decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation